2020
DOI: 10.4067/s0717-75182020000500765
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of school meals provided by PNAE among brazilian public school adolescents

Abstract: and the associated factors among Brazilian adolescents. Methods: Cross-sectional study with data from the Study of Cardiovascular Risks in Adolescents conducted in 2013-2014, with 58,707 adolescents aged 12 to 17 years-old who attended public schools. Logistic regression models were stratified by sex and the significance level of 5% was adopted for all analyses. Results: There was low adherence to school meals (17.2%). The chance of regular consumption of school meals was higher among male adolescents belongin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 11 publications
3
10
1
4
Order By: Relevance
“…Previous studies have shown that the presence of food and beverage sales in schools was associated with an increase in the chances of SSB and ultraprocessed food consumption (16,48). In addition, the presence of this type of sale was associated with a reduction in the chances of consuming school meals provided by the PNAE (49).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that the presence of food and beverage sales in schools was associated with an increase in the chances of SSB and ultraprocessed food consumption (16,48). In addition, the presence of this type of sale was associated with a reduction in the chances of consuming school meals provided by the PNAE (49).…”
Section: Discussionmentioning
confidence: 92%
“…The national literature shows that the factors associated with low adherence to school meals among adolescents are both at the individual level, such as gender, age, race, maternal education, having a paid job, and socioeconomic conditions 16,17,18,19,20,21 , and the school context 17,22 . The presence of a cafeteria 17,22 and poorer student perception of the physical structure of the cafeteria 21 were negatively associated with adherence to school meals.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Sturion et al 17 evaluated 2,678 schoolchildren from the 1st to the 8th grade of elementary education in ten Brazilian municipalities, two from each geographic region, and found that commercial cafeterias in schools are inversely associated with daily adherence to the PNAE. Therefore, the availability and advertising of ultra-processed foods in the school environment influence the adolescents' food choices 5 and can be considered determining factors in the adherence to the food offered by the school, since it has been previously identified that adolescents who regularly buy food from the cafeteria are less likely to adhere to school meals 20 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations